Critical changes in hypothalamic gene networks in response to pancreatic cancer as found by single-cell RNA sequencing - Christian Huisman; Mason A. Norgard; Peter R. Levasseur; Stephanie M. Krasnow; Monique G.P. van der Wijst; Brennan Olson; Daniel L. Marks (Elsevier, 2022)
Objective: Cancer cachexia is a devastating chronic condition characterized by involuntary weight loss, muscle wasting, abnormal fat metabolism, anorexia, and fatigue. However, the molecular mechanisms underlying this syndrome remain poorly understood. In particular, the hypothalamus may play a central role in cachexia, given that it has direct access to peripheral signals because of its anatomical location and attenuated blood-brain barrier. Furthermore, this region has a critical role in regulating appetite and metabolism. Methods: To provide a detailed analysis of the hypothalamic response to cachexia, we performed single-cell RNA-seq combined with RNA-seq of the medial basal hypothalamus (MBH) in a mouse model for pancreatic cancer. Results: We found many cell type-specific changes, such as inflamed endothelial cells, stressed oligodendrocyes and both inflammatory and moderating microglia. Lcn2, a newly discovered hunger suppressing hormone, was the highest induced gene. Interestingly, cerebral treatment with LCN2 not only induced many of the observed molecular changes in cachexia but also affected gene expression in food-intake decreasing POMC neurons. In addition, we found that many of the cachexia-induced molecular changes found in the hypothalamus mimic those at the primary tumor site. Conclusion: Our data reveal that multiple cell types in the MBH are affected by tumor-derived factors or host factors that are induced by tumor growth, leading to a marked change in the microenvironment of neurons critical for behavioral, metabolic, and neuroendocrine outputs dysregulated during cachexia. The mechanistic insights provided in this study explain many of the clinical features of cachexia and will be useful for future therapeutic development.